Survival of two post systems: five-year results of a randomized clinical trial - Schmitter, Marc; Hamadi, Khaled; Rammelsberg, Peter (Quintessence international, 2011)
OBJECTIVE: To assess the survival rate of two different post systems after 5 years of service with a prospective randomized controlled trial. - METHOD AND MATERIALS: One hundred patients in need of a post were studied. Half of the patients received long glass fiber-reinforced posts, while the other half received long metal screw posts. The posts were assigned randomly. After at least 5 years (mean, 61.37 months), follow-ups were established. When a complication occurred prior to this recall, the type and time of the complication was documented. Statistical analysis was performed using the log-rank test and Kaplan-Meier analysis. Additionally, a Cox regression was performed to analyze risk factors. - RESULTS: The survival rate of fiber-reinforced posts was 71.8%. In the metal screw post group, the survival rate was significantly lower, 50.0% (log-rank test, P = .026). Metal posts resulted more often in more unfavorable complications (eg, root fractures); consequently, more teeth (n = 17) had to be extracted. The Cox regression identified the following risk factors: position of the tooth (anterior vs posterior teeth), degree of coronal tooth destruction, and the post system (fiber-reinforced post vs metal screw post). Fiber-reinforced restorations loosened in several patients; in some of these cases (n = 6), patients did not notice this, leading to the extraction of teeth. - CONCLUSION: Long metal screw posts should be used with great care in endodontically treated teeth. Besides the selection of the post system, other factors influence the survival of the restoration.